1999
DOI: 10.1046/j.1365-2028.1999.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of impala (Aepyceros melampus, Lichtenstein, 1812) faecal helminth egg counts through a one‐year period

Abstract: The study was done in Lake Mburo area, Uganda, consisting of Lake Mburo National Park and surrounding ranches. The study involved monitoring changes of output of helminth eggs per gram (e.p.g.) by impala for 12 months. Fresh faecal samples, 178 in total, were collected from the rangeland and subjected to floatation and culture tests. There was a peak faecal e.p.g. output from March to April and from October to November. This period coincided with time of high rainfall and calving peak of impala. There was no f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
(3 reference statements)
3
6
1
Order By: Relevance
“…The month of December in this study also demonstrated a typical ‘rain rise’ in FEC as described in impala in Uganda by Ocaido et al (1999). This may be attributed to early rains rehydrating adverse environment-resistant infective larvae and the favourable environment reactivating hypobiotic larvae, thus increasing infection pressure.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The month of December in this study also demonstrated a typical ‘rain rise’ in FEC as described in impala in Uganda by Ocaido et al (1999). This may be attributed to early rains rehydrating adverse environment-resistant infective larvae and the favourable environment reactivating hypobiotic larvae, thus increasing infection pressure.…”
Section: Discussionsupporting
confidence: 86%
“…The mean monthly FECs from this study are higher than findings by Apio et al (2006) in Uganda, but comparable to findings by Ocaido et al (1999) in impalas in Uganda. The difference between the mean monthly FECs of impala from this study and those from bushbuck in Uganda may be attributable to the fact that the bushbuck were not in captivity and they preferentially browse rather than graze, whereas the converse is true for the impala in this study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…For example, animals show lower kidney fat index or bone marrow fat index in the dry season (Hanks et al 1976;Dunham and Murray 1982;Gallivanetal.1995;Marshal et al 2012). Such seasonal changes are also related to other seasonal observations such as the colonisation of the ruminal epithelium by bacteria (Hill 1982), the seasonal presence of intestinal parasites (Ocaido et al 1999) or the seasonal differences in rumination behaviour (Blanchard and Fritz 2008). In contrast to species from temperate environments, which usually ingest more food when food quality is high (reviewed in Meyer et al 2010), one might expect species from tropical and subtropical environments, with a less pronounced seasonality of body fat stores, to either compensate for reduced diet quality by increasing food intake or at least show less seasonal variation in food intake, as indicated for impala by Meissner et al (1996).…”
Section: Introductionmentioning
confidence: 95%